Quality of life in individuals with spinal cord injury treated in tertiary care centers in Nepal - Parajuli, Bikash; Acharya, Khagendra; Shrestha, Jemina; Dhakal, Raju (Birat Journal of Health Sciences, 2023)
Introduction: Traumatic spinal cord injury (SCI) constitutes a significant challenge to the quality of life (QoL). People with SCI perceive the overall QoL at a lower level in comparison to normal individuals.Objective: This study aims to access the QoL among individuals with SCI and identify factors affecting the QoL.Methodology: This prospective cross-sectional study was done in Dhulikhel Hospital, Kathmandu University Hospital (DH, KUH), and Spinal Injury Rehabilitation Center (SIRC), Sanga, Nepal. All the individuals above 18 years with SCI of at least 3 months from trauma seeking treatment in DH, KUH, or SIRC from June 2019 to May 2021 were included. We utilized the WHO quality of life questionnaires (WHOQOL–BREF) for assessing the QoL.Result: The mean age was 32.95 ± 11.7 years with the majority being males (74.5%). The majority had ASIA Impairment Scale grade A. The social health domain had the highest mean raw and transformed score (13.87 ± 3.13 and 61.7 ± 19.59 respectively). The transformed total QoL score was 50.76±29.76. Only 22 individuals (15.6%) had a transformed total score of > 60 signifying good/ satisfactory QoL.Conclusion: There is a high rate of poor/ unsatisfactory QoL in individuals with SCI in Nepal. Female gender, married status, loss of relative during trauma, ASIA injury severity (AIS) A or B during admission, and no improvement in AIS grade after treatment are significant predictors of poor/ unsatisfactory QoL. Physical health, compared to psychological, social, and environmental health, correlates highest with the transformed total score.